Solution to Q3 of Week 9 Quiz Pool


y[n] = x[n] + 2x[n-1] + 0.5y[n-1]

a. Compute the impulse response h[n] of the system.

$ y[n] = h[n]\text{ when }x[n] = \delta[n] $
$ h[-1] = 0 $
$ h[0] = 1 $
$ h[1] = 2 + 0.5 $
$ h[2] = 0.5(2 + 0.5) $
$ h[3] = 0.5(0.5(2 + 0.5)) $
...
$ h[n] = (0.5 + 0.5) + (0.5 + 2) + (0.5^2 + 2(0.5)^2) + (0.5^3 + 2(0.5)^3) + ... $
So
$ h[n] = 0.5^nu[n] + 2(0.5)^{n-1}u[n-1] $

b. Compute the output when x[n] = u[n].

$ \begin{align} y[n] &= h[n] * x[n] \\ y[n] &= h[n] * u[n] \\ y[n] &= 0.5^nu[n] + 2(0.5)^{n-1}u[n-1] * u[n] \\ y[n] &= (0.5^nu[n] * u[n]) + (2(0.5)^{n-1}u[n-1] * u[n]) \\ \end{align} $

Splitting the expression into two parts, we evaluate them individually,
Using the definition of convolution,
$ (f * g)[n]\ \stackrel{\mathrm{def}}{=}\ \sum_{k=-\infty}^{\infty} f[k]\, g[n - k] $

$ \begin{align} 0.5^nu[n] * u[n] &= \sum_{k=-\infty}^{\infty} 0.5^k u[k] u[n - k] \\ &= \sum_{k=0}^{\infty} 0.5^k u[n - k] \\ &= \sum_{k=0}^{n} 0.5^k u[n] \\ &= u[n] \sum_{k=0}^{n} 0.5^k \\ &= u[n] \frac{1-0.5^{n+1}}{1-0.5} \\ &= 2(1-0.5^{n+1})u[n] \end{align} $

For the next part of the expression convolve with a delta function. Recall, that convolving a function with a shifted delta results in a shifted version of the function,

$ \begin{align} 2(0.5^{n-1}u[n-1]) * u[n] &= 2(0.5^nu[n] * \delta[n-1]) * u[n] \\ &= 2(0.5^nu[n] * u[n]) * \delta[n-1] \\ &= 2(2(1-0.5^{n+1})u[n]) * \delta[n-1] \\ &= 4(1-0.5^{n})u[n-1] \\ \end{align} $

Combining the two,

$ \begin{align} y[n] &= 2(1-0.5^{n+1})u[n] + 4(1-0.5^{n})u[n-1] \end{align} $

c. Compute the output when x[n] = $ 0.25^n $u[n].

$ \begin{align} y[n] &= h[n] * x[n] \\ y[n] &= h[n] * u[n] \\ y[n] &= 0.5^nu[n] + 2(0.5)^{n-1}u[n-1] * 0.25^nu[n] \\ y[n] &= (0.5^nu[n] * u[n]) + (2(0.5)^{n-1}u[n-1] * 0.25^nu[n]) \\ \end{align} $

Splitting the expression into two parts, we evaluate them individually,
Using the definition of convolution,
$ (f * g)[n]\ \stackrel{\mathrm{def}}{=}\ \sum_{k=-\infty}^{\infty} f[k]\, g[n - k] $

$ \begin{align} 0.5^nu[n] * 0.25^nu[n] &= \sum_{k=-\infty}^{\infty} 0.5^k u[k] 0.25^{n-k}u[n - k] \\ &= \sum_{k=0}^{\infty} \left ( \frac{0.5}{0.25} \right )^k 0.25^nu[n - k] \\ &= \sum_{k=0}^{n} 2^k 0.25^nu[n] \\ &= 0.25^nu[n] \sum_{k=0}^{n} 2^k \\ &= 0.25^nu[n] \frac{1-2^{n+1}}{1-2} \\ &= 0.25^n(2^{n+1} - 1)u[n] \\ \end{align} $

For the next part of the expression convolve with a delta function. Recall, that convolving a function with a shifted delta results in a shifted version of the function,

$ \begin{align} 2(0.5^{n-1}u[n-1]) * 0.25^nu[n] &= 2(0.5^nu[n] * \delta[n-1]) * 0.25^nu[n] \\ &= 2(0.5^nu[n] * 0.25^nu[n]) * \delta[n-1] \\ &= 2(0.25^n(2^{n+1} - 1)u[n]) * \delta[n-1] \\ &= 2(0.25^{n-1}(2^{n} - 1))u[n-1] \\ \end{align} $

Combining the two,

$ \begin{align} y[n] &= 0.25^n(2^{n+1} - 1)u[n] + 2(0.25^{n-1}(2^{n} - 1))u[n-1] \end{align} $

Credit: Prof. Bouman


Back to Lab Week 9 Quiz Pool

Back to ECE 438 Fall 2010 Lab Wiki Page

Back to ECE 438 Fall 2010

Alumni Liaison

Abstract algebra continues the conceptual developments of linear algebra, on an even grander scale.

Dr. Paul Garrett